EVALUATION OF PHYSICAL ASPECT OF ISLAMIC RESIDENTIAL CONCEPTS IN THE SHARIA HOUSING PROJECT - Angga Perdana (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2020)
The Republic of Indonesia is the largest Muslim country in the world. In this country the development of shari’a housing is rapidly increasing, this is due to the demand of the shari’a housing market. To meet the needs of consumers having a house with an ideal Islamic residential concept, some criteria can be applied in developing shari'a housing. Many developers have raised the concept of Islamic housing as a branding of developed housing products, but many housings with that concept have not met all the ideal criteria of the concept of Islamic housing. The ideal Islamic residential concept must meet the ideal criteria including there are two entrances, the separation between the service room and the main room, the separation between the family room and living room for the privacy of the occupants, there are parks and open spaces on the residential lots, there are Islamic-style ornaments or plants, there are shading devices, there are ornaments on the main entrance which are the focal points of the entrance design, natural light and ventilation must be able to reach the entire space, carry the concept of climate response, and meet all applicable housing standards. Based on the evaluation results according to investors and in-depth analysis qualitatively and quantitatively about the application of the concept of Islamic housing in the sharia housing case study shows that in the case of Medina Residence 1 it is sufficiently representative to show the application of the ideal Islamic residential concept criteria. Medina Residence 1 received an evaluation response with an average mean score of 5.381on a scale of 6 or it can be said that 89.68% of the criteria for the concept of Islamic housing have been applied well.